Inversed Ratio of CD39/CD73 Expression on γδ T Cells in HIV Versus Healthy Controls Correlates With Immune Activation and Disease Progression - Kolbe, Katharina; Wittner, Melanie; Hartjen, Philip; Hüfner, Anja-Dorothee; Degen, Olaf; Ackermann, Christin; Cords, Leon; Stellbrink, Hans-Jürgen; Haag, Friedrich; Schulze zur Wiesch, Julian (Frontiers in Immunology, 2022)
Background: γδ T cells are unconventional T cells that have been demonstrated to be crucial for the pathogenesis and potentially for the cure of HIV-1 infection. The ectonucleotidase CD39 is part of the purinergic pathway that regulates immune responses by degradation of pro-inflammatory ATP in concert with CD73. Few studies on the expression of the ectoenzymes CD73 and CD39 on human γδ T cells in HIV have been performed to date. Methods: PBMC of n=86 HIV-1-infected patients were compared to PBMC of n=26 healthy individuals using 16-color flow cytometry determining the surface expression of CD39 and CD73 on Vδ1 and Vδ2 T cells in association with differentiation (CD45RA, CD28, CD27), activation and exhaustion (TIGIT, PD-1, CD38, and HLA-DR), and assessing the intracellular production of pro- and anti-inflammatory cytokines (IL-2, TGF-ß, TNF-α, Granzyme B, IL-10, IFN-y) after in vitro stimulation with PMA/ionomycin. Results: CD39 and CD73 expression on γδ T cells were inversed in HIV infection which correlated with HIV disease progression and immune activation. CD39, but not CD73 expression on γδ T cells of ART-treated patients returned to levels comparable with those of healthy individuals. Only a small subset (<1 %) of γδ T cells co-expressed CD39 and CD73 in healthy or HIV-infected individuals. There were significantly more exhausted and terminally differentiated CD39+ Vδ1 T cells regardless of the disease status. Functionally, IL-10 was only detectable in CD39+ γδ T cells after in vitro stimulation in all groups studied. Viremic HIV-infected patients showed the highest levels of IL-10 production. The highest percentage of IL-10+ cells was found in the small CD39/CD73 co-expressing γδ T-cell population, both in healthy and HIV-infected individuals. Also, CD39+ Vδ2 T cells produced IL-10 more frequently than their CD39+Vδ1 counterparts in all individuals regardless of the HIV status. Conclusions: Our results point towards a potential immunomodulatory role of CD39+ and CD73+ γδ T cells in the pathogenesis of chronic HIV infection that needs further investigation.